The Complexity of Insurance Underwriting Results Through Artificial Intelligence Navigation - Tammana, Praveen Kumar (Journal of Research in Science and Engineering, 2025)
Insurance underwriting is the backbone of the insurance industry. It's the method through which insurers assess risk and determine the viability of insurance policies. The results of underwriting dictate the financial health and success of insurance companies. In this article, we will explore into the intricacies of underwriting results and how they shape the landscape of the insurance business. Understanding Underwriting Results: Underwriting results are calculated by subtracting incurred losses and underwriting expenses from the earned premium. In essence, it's the profit generated from underwriting activities before investment income is considered. A positive underwriting result, often referred to as an underwriting profit, indicates that the insurer has successfully assessed and priced the risks it has assumed. The Significance of Underwriting Profitability: The sustainability of an insurance company largely hinges on its ability to underwrite risks profitably. While investment income can help bolster the company's financial standing, reliance on such is fraught with market volatility. Thus, consistent underwriting profitability ensures that an insurance company can meet its claim obligations without undue reliance on investment earnings.